Prevalence and factors associated with overweight and obesity among patients with type 2 diabetes mellitus in Uganda—a descriptive retrospective study - Pontiano Kaleebu; Moffat Nyirenda; Salome Tino; Billy N Mayanja; Michael Charles Mubiru; Emmanuel Eling; Edward Ddumba (BMJ Open)
Objectives To assess the prevalence and risk factors of overweight and obesity among type 2 diabetes mellitus (T2DM) patients in Uganda.Design Retrospective chart review.Setting This study was conducted in the outpatient’s T2DM clinic in St. Francis Hospital—Nsambya, Uganda between March and May 2017.Participants Type 2 diabetes patients registered in the diabetes clinic between July 2003 and September 2016.Outcome measures Overweight and obesity defined as body mass index (kg/m2) of 25.0–29.9 and obesity as 30.0 or higher.Results Of 1275 T2DM patients, the median age was 54 (IQR: 44–65) years, 770 (60.40%) were females, 887 (69.6%) had hypertension, 385 (28%) had controlled glycaemia, 349 (27%) were obese, while 455 (36%) were overweight. Overweight/obesity were lower among men (OR: 0.45, 95% CI: 0.340 to 0.593, p≤0.001) and among patients aged ≥65 years (OR: 0.52, 95% CI: 0.350 to 0.770, p=0.001); patients who rarely ate fruits and vegetables (OR: 0.66, 95% CI: 0.475 to 0.921, p=0.014) but higher among patients of middle (OR: 1.83, 95% CI: 1.320 to 2.550, p≤0.001) and upper (OR: 2.10, 95% CI: 1.450 to 2.990, p≤0.001) socioeconomic status; on dual therapy (OR: 2.17, 95% CI: 1.024 to 4.604, p=0.043); with peripheral neuropathy (OR: 1.40, 95% CI: 1.039 to 1.834, p=0.026) and hypertension (OR: 1.70, 95% CI: 1.264 to 2.293, p≤0.001).Conclusions Overweight and obesity are high among T2DM patients in this population and may contribute significantly to poor outcomes of T2DM. Therefore, strategies to address this problem are urgently needed.